A Highly Efficient In Vitro Site-directed Mutagenesis Protocol for Introducing Multiple-site Mutations into Target Genes - Fanrong MENG; Chen CHEN; Yongwen LI; Haisu WAN; Qinghua ZHOU (Chinese Journal of Lung Cancer, 2014)
Background and objective The methods for introducing point mutations into target genes are important for dissecting the relationship of gene structure and function. Up to date, there are numbers of protocols available for the purpose. However, many of them are suited for introducing single site mutation into the target gene. For introducing multiple-site mutations simultaneously into the target genes, it is required to further improve the related methods. Methods In this report, we describe an improvement on the type IIs restriction enzyme-dependent site-directed mutagenesis method and the improved protocol is highly efficient for multiple-site mutagenesis. In our method, a pair of mutagenic primers are synthesized for each desired site and each mutagenic primer contains a selected type IIs restriction site. The DNA fragments between two neighboring sites are amplified with PCR. All amplified fragments are then digested by the selected Type IIs restriction enzyme. The expected mutant is eventually generated by ligation of these digested DNA fragments. Results The improved protocol is very easy and can be achieved in just one day. As a proof of principle, we have introduced multiple-site, i.e., 3-site or 4-site mutations into the fusion gene of nm23 and EGFP (enhanced green fluorecence protein). The mutagenic frequencies are almost reached 100%. Conclusion Our protocol provides a useful tool for gene function research.